Exfoliablity, magnetism, energy storage and stability of metal thiophosphate nanosheets made in liquid medium. (22nd February 2023) - Synnatschke, Kevin; van Dinter, Jonas; Müller, Alina; Tiede, David; Spillecke, Lena; Shao, Shouqi; Kelly, Daniel; Konecny, Jan; Konkena, Bharathi; McCrystall, Mark; Saigal, Nihit; Wurstbauer, Ursula; et al.
Abstract: The family of antiferromagnetic layered metal hexathiohypo diphosphates, M2 P2 S6 represents a versatile class of materials, particularly interesting for fundamental studies on magnetic properties in low dimensional structures, and yet exhibiting great potential for a broad variety of applications including catalysis, energy storage and conversion, and spintronics. In this work, three representatives of this family of 2D materials (M = Fe, Ni, and Mn) are exfoliated in the liquid phase under inert conditions and the nanosheet's properties are studied in detail for different sizes of all three compounds. Centrifugation-based size selection is performed for this purpose. The exfoliability and structural integrity of the nanosheets is studied by statistical atomic force microscopy and transmission electron microscopy measurements. Further, we report size and thickness dependent optical properties and spectroscopic metrics for the average material dimensions in dispersion, as well as the nanomaterials' magnetic response using a combination of cryo-Raman and superconducting quantum interference device measurements. Finally, the material stability is studied semi-quantitatively, using time and temperature dependent extinction and absorbance spectroscopy, enabling the determination of the materials' half-life, portion of reacted substance and the macroscopic activation energy for the degradation.